Interests and Challenges of the Ivanishvili Government vis-à-vis Azerbaijan - Veliev, Samir (ADA University, 2013)
After the Rose revolution in Georgia in 2003, the economic, political, strategic relations between Azerbaijan and Georgia further developed. More regional projects, more investment and business flowing from Azerbaijan closely connected the two. Importance of these two neighboring countries for each other challenges and prospers their long-run strategic relations. Azerbaijani oil and gas resources are transported through Georgian territory to the markets in the Mediterranean. Moreover, construction of other projects such as Baku-Tbilisi-Kars railroad system is going to be built through Georgia. As an oil-rich country Azerbaijan expands its energy markets and invests internationally in many different countries through particular channels such as State Oil Company of Azerbaijan Republic (hereafter SOCAR). In recent years, SOCAR has been expanding its scope of activity areas ranged from oil drilling to gas supply and education. Increasing oil revenues and share in oil production under the Contract of the Century improve SOCAR’s capacities to go beyond borders of Azerbaijan. Now SOCAR operates not only in neighboring Georgia. SOCAR invests in constructing petroleum stations, gas supply, petro chemicals, port-terminals and some social projects in those countries. SOCAR petrol stations were launched in serving and distribution of energy resources in Georgia in November 2006. SOCAR established its own representation in Georgia. Its main goals are protecting company interests in terms of economic affairs, creating supportive environment for company projects and coordinating efforts of interested parties. It is concerned with interrelations with government bodies, negotiations with legal entities, sponsorships and charity in Georgia (SOCAR Representation, 2012) However, domestic politics of Georgia is less stable, and more open to changes of powers compared with Azerbaijan. Emergence of relatively new opposition in Georgian politics under Bidzina Ivanishvili – Georgian Dream strongly challenged Saakashvili’s United National Movement in parliamentary elections in October 2012. Saakashvili’s ruling party lost the elections to Georgian Dream, and Bidzina Ivanishvili became the prime minister of Georgia (Central Election Commission of Georgia, 2012). Being elected and gaining power to govern the country gives Georgian Dream opportunity to challenge Saakashvili, and investigate postrevolutionary period in order to find misappropriated funds or corrupted policy implementations. These findings might be significant for Georgian Dream to overcome United National Movement in the upcoming presidential elections in 2013. On the other hand, United National Movement’s seats in the Parliament and the president’s constitutional right to veto the Government give Saakashvili to exert its power to challenge the Ivanishvili Government. Ivanishvili promised lower prices of fuel and gas to the public during his political campaign (Rusiko Machaidze, 2012), when he highlighted the need for negotiations with SOCAR on that point. It was clear that all those promises were calculated to get credits of Saakashvili’s backscene politics. His statement about the economic inefficiency of Baku-Tbilisi-Kars railroad (Vestnik Kavkaza, 2012) construction may be seen as a result of economic benefits of the project considering the transportation system of Georgia. Further, demands of higher salaries and less discriminative policies of employees of Kulevi Terminal which is owned by Azerbaijan was another issue of Ivanishvili. All these factors seem to affect relations of the two neighbors. This paper will focus on Ivanishvili’s approaches and statement about calculations, and reviewing developments of relations with Azerbaijan in the context of particular regional, bilateral, and domestic circumstances of the two countries.
Keywords: Georgia (Republic) -- Politics and government; Georgia (Republic) -- Foreign relations; Georgia (Republic) -- Social conditions; Public and International Affairs